Experimental study on the seismic performance of RC columns retrofitted by lap-spliced textile-reinforced mortar jackets after high-temperature exposure. (15th January 2021) - Park, Sang-Hyun; Dinh, Ngoc Hieu; Um, Jung-Woo; Choi, Kyoung-Kyu
Highlights: Investigate the seismic performance of RC columns retrofitted by TRM after high temperature exposure. Practical retrofitted solutions were applied by using TRM composite materials. The damage after high temperature exposure was evaluated by ultrasonic image scanning. An analytical model of idealized backbone curves was developed and verified with the test results. Abstract: The present experimental study investigated the seismic performance of reinforced concrete columns retrofitted by lap-spliced TRM jackets after high-temperature exposure. A total of eight column specimens were fabricated and tested, with the two main parameters being the amount of carbon fiber mesh, and the surface treatment method in lap-sliced regions. High-temperature tests were performed in a furnace chamber with moderate temperature up to 250 °C, followed by ultrasonic image scanning and cyclic loading tests. The experimental results from ultrasonic image scanning and cyclic loading tests illustrate that even after exposure to high temperature, the retrofitted solution using TRM jackets with the proposed lap-spliced details was effective, in terms of increasing both the strength and the deformation capacity. In addition, an analytical model to evaluate idealized backbone curves used for nonlinear analysis of columns retrofitted by TRM jackets subjected to high temperatures was proposed and showed reasonable agreement with the experimental results.